The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1016/s0735-1097(01)01663-1
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular mass and cardiovascular morbidity in essential hypertension: the MAVI study

Abstract: Our findings show a strong, continuous and independent relationship of LV mass to subsequent cardiovascular morbidity. This is the first study to extend such demonstration to a large nationwide multicenter sample of uncomplicated subjects with essential hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
200
1
11

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(221 citation statements)
references
References 29 publications
7
200
1
11
Order By: Relevance
“…The limit of statistical significance was set at Po0.05 by two-tailed tests. 16,17,23,29,40 3 interventional prospective trials 13,30,34 and the remaining 2 were performed in specialist out-patient centers. 19,42 In approximately half of the studies, the effective observation period, including the echocardiographic examination, was before the year 2000.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limit of statistical significance was set at Po0.05 by two-tailed tests. 16,17,23,29,40 3 interventional prospective trials 13,30,34 and the remaining 2 were performed in specialist out-patient centers. 19,42 In approximately half of the studies, the effective observation period, including the echocardiographic examination, was before the year 2000.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,17,19,21,24 --26,28,36 In contrast, LVH ranged from 43.6 to 52.8% (P ¼ 0.03 for comparison between more sensitive criteria) in the four studies (n ¼ 6427) with the highest proportion of patients on antihypertensive treatment (X85%). 16,29,35,40 Table 3 shows the findings of 13 studies (n ¼ 16 033 patients) providing LVH rates according to a gender-based analysis. 13,14,17,21,22,24,28,30 --32,36,38,40 In 8 out of 12 studies, LVH prevalence was higher in women; in 2 reports the trend was opposite and in the remaining 3 LVH was more prevalent in men according to some but not all criteria.…”
Section: Prevalence Of Lvhmentioning
confidence: 99%
“…LVH can adversely impact on the quality of life and heralds increased risk of cardiovascular morbidity and mortality. 2 However, a recently published meta-analysis showed that not all classes of antihypertensive drugs are equally effective in reversing LVH. 19 In the present study, ABPM showed that telmisartan significantly lowered 24-h mean SBP and DBP.…”
Section: Discussionmentioning
confidence: 99%
“…1 Therefore, left ventricular hypertrophy (LVH) regression is a key objective when managing hypertensive patients, the risk of cardiovascular disease being reduced in patients with LVH regression compared with those with none. 2 According to a meta-analysis published in 1992, 3 ACE inhibitors produced the greatest reduction in LVM, despite the blood pressure reductions produced by other classes of antihypertensive agents F beta-blockers, calcium channel blockers and diuretics F being equivalent to those of ACE inhibitors. As a class, ACE inhibitors are well recognised as being effective in the treatment of hypertension and relatively well tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] The presence of LVH, in turn, constitutes an important independent factor for cardiovascular risk in patients with CKD. 7,8,12,13 Patients in renal replacement therapy (stage V) 6 may have larger or smaller residual renal function (RRF) declines depending on the diastolic method used. 14 Thus, patients on hemodialysis (HD) had more rapid reductions in their RRF than those on peritoneal dialysis (PD).…”
Section: Introductionmentioning
confidence: 99%